ANALISIS PENGETAHUAN MASYARAKAT NON MUSLIM TERHADAP PERBANKAN SYARIAH DI KABUPATEN SERANG DAN KOTA SERANG - Khristina Sri Prihatin; Uun Fiana (FKIP, Universitas Banten Jaya, 2021)
This study aims to determine how the condition of knowledge / understanding of Non Muslim Communities of Islamic Banking in the District of Serang and the City of Serang.This research uses which are conducted by using questionnaires to 100 people (samples) Non Muslim who are spread in Serang Regency and Serang City. Of the 100 questionaires of 5 groups of Non Muslim Religions, Namely : Protestanstism, Katholicism, Hinduism, Buddhism And Confucianism.The results of this study indicate that the Non Muslim Community’s knowledge of Islamic Banking is still very limited, most respondents only know the location of the spread of Islamic Banking in their area and only know the term revenue sharing without knowing how the system works in Islamic Banking. Knowledge of the characteristics of banking is still limited to knowing the term but does not yet know of any promotions carried out by Islamic Banking directly. Knowledge of non-Muslim communities has an effect between variables X1 and X2 together on Y1 of 70.4% while the influence of variables X1 and X2 together on Y2 is 80.6% and the value of F arithmetic > F table is 90, 20 > 3.09 and 47.92 > 3.09 then the hypothesis of both effects is accepted.